Implementing Group CBT for Depression Among Latinos in a Primary Care Clinic. Issue 1 (February 2018) - Aguilera, Adrian; Bruehlman-Senecal, Emma; Liu, Nancy; Bravin, Julia
Abstract: Depression in low-income Latino populations can be treated using group cognitive behavioral therapy (GCBT). However, effective delivery of GCBT for depression in primary care settings is often impeded by high dropout rates and poor homework adherence. In this study, we describe the structure, processes, and outcomes (including attendance, homework completion, and symptom measures) of GCBT for Spanish-speaking Latino patients with depression in an urban public sector primary care setting. For this study, 96 Latino patients in a primary care clinic participated in at least 1 session of GCBT. Although depressive symptoms among these patients, as measured by the PHQ-9, significantly decreased during treatment, attendance and homework completion were limited. Even with a strategy in place to allow patients to continue in treatment after missing several sessions, 23% of patients dropped out of therapy following their initial session, and approximately half of all patients completed less than 50% (or 8) therapy sessions. Homework was only completed 23% of the time it was checked. Greater session attendance prospectively predicted lower depressive symptoms over time. We discuss potential strategies to increase engagement, treatment effects, and symptom reduction for depression in primary care settings. Highlights: Implementation challenges of GCBT for Spanish-speaking Latinos in a public sector primary care clinic are described. Primary care–based GCBT showed significant reductions in depression scores. Greater session attendance prospectively predicted lower depressive symptoms over time. Future directions to increase attendance such as integrating technology into treatment are discussed.